Citric acid strongly inhibits visceral pain response in mice - Abdel-Salam, Omar M. E.; Baiuomy, Ayman R. (Technische Universität Dortmund, 2008)
Citric acid introduced into the stomach of mice at increasing concentrations of 0.1, 1 or 10 % (4.8 µM-0.48 mM; 95 µmol/kg-9.5 mmol/kg, 0.5 ml) caused dose-dependent inhibition of abdominal constrictions induced 1 h later by i. p. acetic acid injection by -51 % to -69.5 %. When administered at 10 % (0.48 mM, 0.5 ml) 15 min before nociceptive challenge, citric acid inhibited the nociceptive response by 96.8 %. Inhibition of the acetic acid-induced abdominal constrictions was also observed when lower doses of citric acid were introduced into the stomach (0.2 ml of 0.1-1 %; 38.1 µmol/kg-0.38 mmol/kg). The effect was evident as early as 5 min after administration of citric acid into the stomach and with the maximal effect being at 15-30 min after dosing. Lidocaine given orally 5 min prior to citric acid (1 %, 48 µM; 0.38 mmol/kg, 0.2 ml) prevented antinociception by citric acid, but lidocaine given 15 min before oral introduction of citric acid enhanced the citric acid-induced inhibition of the nociceptive response to acetic acid. The antinociceptive effect of orally administered citric acid (1 %, 48 µM; 0.38 mmol/kg, 0.2 ml) was increased by pre-treatment with propranolol (4 mg/kg, s. c.), yohimbine (4 mg/kg, s. c.), guanethidine (32 mg/kg, s. c.), but reduced after treatment with atropine (3 mg/kg, s. c.), which itself increased the nociceptive behavior. Similar inhibition of the acetic acid-induced nociceptive behavior was also observed when sodium citrate (pH 7.21) or 0.1 N HCl (pH 3) or 1 % sucrose solution (0.2 ml) was intragastrically given. It is suggested that citric acid might act to stimulate sensory afferents and that transmission of nociceptive information centrally leads to the activation of descending antinociceptive mechanism to a noxious stimulus.
EXCLI Journal ; Vol. 7, 2008
Keywords: citric acid; intraperitoneal acetic acid; mice; visceral nociceptive pain; 610